PERAN DISPUTE SETTLEMENT BODY (DSB) DALAM PENYELESAIAN SENGKETA TARIF ALUMINIUM AMERIKA SERIKAT-INDIA (DS547) - Nengsih, Sri Bunga Wahyu; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
India sued the United States in the World Trade Organization (WTO) regarding the DS547 aluminum import tariff policy. The United States' policy affected India's economy in aluminum exports to the United States. The tariff policy violated Articles 11(a) and 11(b) of the GATT 1994 concerning commitments on import duties, imports, and exports. The dispute resolution process was carried out through the Dispute Settlement Body (DSB). The DSB is responsible for establishing a panel and recommending a final decision. The dispute was resolved through a mini-trade deal approach with a focus on reciprocal tariff reductions. The reason the United States and India agreed to the mini-trade deal was that both countries agreed to end trade tensions for strategic and economic reasons. The United States agreed to revoke the policy, and India agreed to withdraw the issue and not seek compensation from the United States, thus opening up broader market opportunities. Keywords: DSB, WTO, Tariff, Aluminum.